Echoes of Medieval and Pre-Modern Animal Trials in the Interlude Declamatio sub forma iudicii (1735) - Czarnowus, Anna (Romanica Silesiana, 2021)
Declamatio sub forma judicii can be found in the Graudenz Codex (1731–1740). It is an interlude that jokingly reports an animal trial. The interlude is a humorous treatment of the historical trials on animals that continued from the Middle Ages to the eighteenth century. On the one hand, such eighteenth-century discussions of animal trials continued the medieval tradition. This would confirm the diagnosis about the existence of the “long Middle Ages”, especially in Central and Eastern Europe, where the cultural trends could be somehow belated in comparison to those in the West. On the other hand, perhaps writing about animal trials in the eighteenth century was already a form of medievalism. High culture propagated anthropocentrism in its thinking about animals, while folk culture entailed anthropomorphism. In animal trials animals are treated as subjects to the same regulations as humans, which means that they were seen as very much similar to humans. The eighteenth-century interlude recreates this tradition, but it is a source of satirical laughter.